Inflammatory and metabolic markers mediate the association between urinary metals and non-alcoholic fatty liver disease in U.S. adults: a cross-sectional study - Li, Shu-yue; Lv, Jia-jie; Yang, Xi-tao; Yang, Cheng-hao; Yin, Min-yi (Frontiers in Public Health, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) is a global public health problem. Inflammation, oxidative stress, and insulin resistance are involved in the development and progression of NAFLD. Although the etiology of NAFLD remains unclear, environmental factors are increasingly recognized as non-negligible risk factors. This study was to evaluate the urine metal associated with the risk of NAFLD and inflammation and metabolic markers mediating role.MethodsAccording to the national health and nutrition examination survey (NHANES), to detect the metal concentration in the urine of 3,948 U.S. adults, including barium (Ba), cadmium (Cd), cobalt (Co), and cesium (Cs), molybdenum (Mo), lead (Pb), antimony (Sb), thallium (Tl), and uranium (Tu). Multivariate logistic regression and weighted (WQS) and quantile regression were used to investigate the single and mixed metals associated with the risk of NAFLD. In addition, inflammatory and metabolic markers may mediate the relationship between metals and NAFLD. Inflammatory markers included neutrophil albumin ratio (NPAR) and neutrophil-to-lymphocyte ratio (NLR). The fatty liver index (FLI) was used as a liver metabolic marker. Mediation analysis aimed to investigate the mediating effects of inflammation and metabolism on the association between metals and NAFLD risk.ResultsIn the single-exposure model, Ba, Cd, Cs, Mo, Tl, and Tu were identified to be positively associated with NAFLD risk, with odds ratios (OR) ranging from 1.29 to 1.48 (all P < 0.05). Mixed exposure analysis showed consistent associations (OR: 1.48, 95% CI: 1.06 to 2.06). In addition, Ba, Cd, Mo, Pb, and Tu and negatively correlated with inflammatory markers, but was positively correlated with hepatic metabolism markers. At the same time we have found that inflammatory markers and negative correlation with NAFLD, and hepatic metabolism markers are positively correlated with NAFLD risk relationship (P < 0.05). Further mediation analysis showed that the associations of single metals (mainly Mo, Ba, and Tu) and mixed metals with NAFLD risk were mediated in parallel by the above-mentioned inflammatory and metabolic markers, with the mediating proportions ranging from 16.89% to 69.39% (all P < 0.05). Show that metal concentration can reduce serum inflammatory markers in the urine and raise levels of metabolites markers and then induce NAFLD.ConclusionThese findings suggest that exposure to the metal can increase the risk of NAFLD, this may be partly mediated by inflammation and metabolic markers. Clinically, this highlights the importance of monitoring environmental metal exposure and addressing inflammation and metabolic dysfunction as potential intervention targets to reduce NAFLD risk.